Numbered Head Together Learning Model (NHT) In Improving Student Learning Outcomes in Social Sciences Subjects Class VII UPTD SMP Negeri 7 Pematang Siantar FY 2023/2024 - Yesika Raya Hutagaol; Debbi Petra Manahara Sitorus; Binsar Tison Gultom (International Journal of Integrated Science and Technology, 2023)
Numbered Head Together Learning Model (NHT) In Improving Student Learning Outcomes in Social Sciences Subjects Class VII UPTD SMP Negeri 7 Pematang Siantar T.A 2023/2024.